Survival of aging CD264(+) and CD264(−) populations of human bone marrow mesenchymal stem cells is independent of colony-forming efficiency - Madsen, Sean D. (Biotechnol Bioeng, 2019)
In vivo mesenchymal stem cell (MSC) survival is relevant to therapeutic applications requiring engraftment and potentially to non-engraftment applications as well. MSCs are a mixture of progenitors at different stages of cellular aging, but the contribution of this heterogeneity to the survival of MSC implants is unknown. Here, we employ a biomarker of cellular aging, the decoy TRAIL receptor CD264, to compare the survival kinetics of two cell populations in human bone marrow MSC (hBM-MSC) cultures. Sorted CD264(+) hBM-MSCs from two age-matched donors have elevated β-galactosidase activity, decreased differentiation potential and form in vitro colonies inefficiently relative to CD264(−) hBM-MSCs. Counterintuitive to their aging phenotype, CD264(+) hBM-MSCs exhibited comparable survival to matched CD264(−) hBM-MSCs from the same culture during in vitro colony formation and in vivo when implanted ectopically in immunodeficient NIH III mice. In vitro and in vivo survival of these two cell populations were independent of colony-forming efficiency. These findings have ramifications for the preparation of hBM-MSC therapies given the prevalence of aging CD264(+) cells in hBM-MSC cultures and the popularity of colony-forming efficiency as a quality control metric in preclinical and clinical studies with MSCs.